DISAIN PERBANDINGAN KARAKTERISTIK TURBIN SNAIL-LIE 4 SNAIL DAN 8 SNAIL PADA PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO (PLTMH) - Dwiki Dharma Putra, Ida Bagus; Jasa, Lie; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2020)
is one of the regions with potential renewable energy sources, including hydropower, namely the Micro Hydro Power Plant (PLTMH). The main problem with hydropower is the flow of water that does not flow continuously throughout the year. A micro hydro that is placed in a certain location requires a turbine in accordance with the characteristics of the existing location. In this study, a turbine was designed to obtain a new type of Snail-Lie turbine that accommodates all existing location parameters. In this turbine, there are variations in the form of gaps or spaces in each particular blade to trap water so that it can increase the torque, where this torque will affect the turbine output. The research method used is to find mathematical models of the Snail-Lie 4 Snail and 8 Snail turbines, make a prototype model to be tested in the laboratory, make a real Snail-Lie turbine model for field trials. The results showed that the addition of the number of snails from 4 snails to 8 snails caused the turbine's performance to increase, this is because the number of snails will affect the performance of the turbines, because the snail functions as a water trap so that it can be used as thrust for the turbine when it rotates. The highest output obtained is at the nozzle position 0° and the nozzle angle of 20° using a snail-lie 8 snail tubing which produces 166.9 rpm turbine rotation, 1086.8 rpm generator rotation, 0.707 volt generator voltage, 0.189 watt generator power, and torque amounting to 0.01 Nm, and an efficiency of 20.8%. The low efficiency value obtained in the system is 20.8% because the water entering the turbine is not comprehensive, the slip occurs in the turbine that is coupled with the generator through the fan rope and the generator has its own efficiency.